Strengthening Adolescent Sexual Health Literacy through Targeted Educational Interventions in German Secondary Schools - Gunda Waldmann; Michael Neureiter; Stefan Zippel; Corbinian Fuchs (Journal of Cancer Education, 2026)

Expression of protein kinase A catalytic subunits in healthy and diseased mouse kidneys - Sally Fuchs; Michael Majer; Yuliang Ma; Manuela Harloff; Susan Taylor; Jens Schlossmann (Pflügers Archiv - European Journal of Physiology, 2026)
Diabetic nephropathy (DN) is characterized by a decline in renal function resulting from hyperglycaemia and is often requiring dialysis or renal transplantation. Yet, the signalling events causing DN and the effective treatment options are poorly understood. Changes in the signalling of cyclic nucleotides and their regulated kinases are hypothesized to be involved in its development. Protein kinase A (PKA) signalling pathways are known to modulate extracellular matrix metabolism and exert antifibrotic effects. Multiple isoforms of PKA regulatory and catalytic subunits exist, leading to functional specificities of the kinase arising from different combinations of these isoforms. However, localization of the specific PKA subunits, as well as other signalling proteins involved in this pathway, still need to be explored comprehensively. To gain an overview about PKA distribution, kidneys were analysed by immunohistochemistry and stained for different PKA subunits. Type 1 diabetes was induced by streptozotocin in wildtype (WT) and endothelial NOS knockout (eNOS-KO) mice. The catalytic subunit expression was quantified and compared between healthy and diabetic kidneys. Analysis of expression patterns of the PKA catalytic subunits Cα and Cβ reveal differences across segments of the kidney and in intracellular localization. Cα exhibited ubiquitous expression in all renal cell types. In contrast, Cβ only shows a high expression in proximal tubules, while its expression in other segments is comparatively weak. No significant changes in Cα or Cβ expression are detectable in diabetic mice or eNOS-KO mice compared to WT mice.

Quantifying quaternary climate variability in the Southern Caucasus using land snail shell isotope transfer functions and climatic niche modeling - Christiane Richter; Michael Schneider; Daniel Wolf; Frank Walther; Bernhard Hausdorf; Hayk Hovakimyan; Lilit Sahakyan; Markus Fuchs; Dominik Faust (Quaternary Science Reviews, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Warming-induced destabilization of polar coastal rock cliffs and the role of thermokarst: A case study of Forkastningsfjellet on Svalbard - Dirk Kuhn; Reginald L. Hermanns; Michael Fuchs; Nick Schüßler; Jewgenij Torizin; Juditha Aga; Jacob Bendle; Trond Eiken; Dirk Balzer (Science of The Total Environment, 2025)

Project ‘‘Mass Movements in Germany’’ and its implications for nationwide landslide susceptibility assessment - Jewgenij Torizin; Michael Fuchs; Dirk Balzer; Dirk Kuhn; Stefan Glaser; Dominik Ehret; Johannes Wiedenmann; Peter Dommaschk; Stefan Henscheid; Roland Strauß (Bulletin of Engineering Geology and the Environment, 2024)
The paper presents the framework and discusses the outcomes of the "Mass Movements in Germany" project—a collaboration of five State Geological Surveys (SGSs) and the Federal Institute for Geosciences and Natural Resources (BGR) to conduct a feasibility study for a nationwide landslide susceptibility map in Germany using harmonized datasets. Therefore, distinct methods representing heuristic, physically-based, and data-driven approaches were employed. In 14 consecutive modeling cases, we investigated parameter selection and preparation, model building, evaluation, and transferability issues. The results show that nationally harmonized datasets, deemed high-quality, exhibited data generalization at regional scales, affecting the reliability of the landslide susceptibility patterns. While using regional datasets on larger scales mitigated some generalization effects, heterogeneities in inventory datasets among distinct federal states pose challenges in creating a nationwide applicable model. Heterogeneous data require locally adjusted model designs affecting the model's transferability and comparability of data-driven models across large regions. Heuristic methods operate without observational data but require in-depth knowledge of the regional-geological conditions by involving expert groups rather than single experts. The physically-based model shows promising results with parametrization based on the pedotransfer functions and soil database supplementing the national soil map. However, this approach is limited to shallow translational landslides. Thus, considering all mass movement types, a single comprehensive approach for creating a nationwide landslide susceptibility map for Germany is currently not feasible. Close collaboration and further harmonization of datasets and methods involving all SGSs are needed.

The holocentricity in the dioecious nutmeg (Myristica fragrans) is not based on major satellite repeats - Yi-Tzu Kuo; Jacob Gigi Kurian; Veit Schubert; Jörg Fuchs; Michael Melzer; Ananthu Muraleedharan; Ravi Maruthachalam; Andreas Houben (Chromosome Research, 2024)
Holocentric species are characterized by the presence of centromeres throughout the length of the chromosomes. We confirmed the holocentricity of the dioecious, small chromosome-size species Myristica fragrans based on the chromosome-wide distribution of the centromere-specific protein KNL1, α-tubulin fibers, and the cell cycle-dependent histone H3 serine 28 phosphorylation (H3S28ph) mark. Each holocentromere is likely composed of, on average, ten centromere units, but none of the identified and in situ hybridized high-copy satellite repeats is centromere-specific. No sex-specific major repeats are present in the high-copy repeat composition of male or female plants, or a significant difference in genome size was detected. Therefore, it is unlikely that M. fragrans possesses heteromorphic sex chromosomes.

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Conceptualizing sustainable participation in the context of German football supporters - Sebastian Björn Bauers; Sandy Adam; Michael Fuchs; Leon Piotrowski; Gregor Hovemann (German Journal of Exercise and Sport Research, 2024)
Institutionalized supporter participation is a traditional part of German professional football clubs. Due to commercialization, some challenging issues have arisen in recent years regarding supporter participation. To develop new approaches for improving participation, the study uses a social sustainability perspective, illustrating that social sustainability elements help to develop and structure the potential for improvement of participation in German professional football. By identifying and discussing links between social sustainability and institutionalized supporter participation, we contribute to the conceptualization of sustainable participation. Our research supports the creation of an inclusive and sustainable fan community where fans can actively participate in decisions and actions that affect their current and future fandom environment. Based on the social sustainability principles of health, influence, competence, impartiality, and meaning-making, we compile the following characteristics of sustainable participation: social well-being oriented participation, direct influence, regular voting rights, representative participation, appealable resolutions, information-based participation, barrier-free participation, democratic voting, established constitutions, and encouraged participation. This conceptualization provides approaches and foundations for future investigations regarding participation research in football and practical implications for member associations, association members, league organizers, and other stakeholders to establish and improve institutionalized participation.

Chiral-based mechanical metamaterial with tunable normal-strain shear coupling effect - Mathias Fleisch; Andreas Thalhamer; Gerald Meier; Philipp Arno Franz Huber; Peter Filipp Fuchs; Gerald Pinter; Sandra Schlögl; Michael Berer (Engineering Structures, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Miscibility in systems containing (poly(oxymethylene) ethers (OME) + hydrocarbons + water) - Christian F. Breitkreuz; Alexander Holzer; Thorsten Fuchs; Michael Günthner; Hans Hasse (Fuel, 2023)

Characterizing U.S. drought over the past 20 years using the U.S. drought monitor - Ronald D. Leeper; Rocky Bilotta; Bryan Petersen; Crystal J. Stiles; Richard Heim; Brian Fuchs; Olivier P. Prat; Michael Palecki; Steve Ansari (International Journal of Climatology, 2022)
The main challenge of evaluating droughts in the context of climate change and linking these droughts to adverse societal outcomes is a lack of a uniform definition that identifies drought conditions at a location and time. The U.S. Drought Monitor (USDM), created in 1999, is a well‐established composite index that combines drought indicators across the hydrological cycle (i.e., meteorological to hydrological) with information from local experts. This makes the USDM one of the most holistic measures for evaluating past drought conditions across the United States. In this study, the USDM was used to define drought events as consecutive periods in time where the USDM status met or exceeded D1 conditions over the past 20 years. This analysis was applied to 5 km grid cells covering the U.S. and Puerto Rico to characterize the frequency, duration, and intensification rates of drought, and the timing of onset, amelioration, and other measures for every drought event on record. Results from this analysis revealed stark contrasts in the evolution of drought across the United States. Over the western United States, droughts evolved much slower, resulting in longer‐lasting but fewer droughts. The eastern United States experienced more frequent, shorter‐duration events. Given the slower evolution from onset to drought peak, flash droughts, which made up 9.8% of all droughts, were less common across the western United States, with a greater frequency over the southern United States. The most severe drought event on record was the 2012 drought, when more than 21% of the United States experienced its largest number of weeks at or above extreme (D3) drought conditions. The availability of historical drought events would support future societal impacts studies relating drought to adverse outcomes and aid in the evaluation of mitigation strategies by providing a dataset to local decision makers to compare and evaluate past droughts.

Patient-Reported Outcome Severity and Emotional Salience Network Disruption in Multiple Sclerosis - Tom A. Fuchs; Caila B. Vaughn; Ralph H. B. Benedict; Bianca Weinstock-Guttman; Niels Bergsland; Dejan Jakimovski; Deepa Ramasamy; Robert Zivadinov; Michael G. Dwyer (Brain Imaging and Behavior, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Investigation of landslides with natural lineaments derived from integrated manual and automatic techniques applied on geospatial data - Simon Sadiq; Umar Muhammad; Michael Fuchs (Natural Hazards, 2022)

Degrading permafrost river catchments and their impact on Arctic Ocean nearshore processes - Paul J. Mann; Jens Strauss; Juri Palmtag; Kelsey Dowdy; Olga Ogneva; Matthias Fuchs; Michael Bedington; Ricardo Torres; Luca Polimene; Paul Overduin; Gesine Mollenhauer; Guido Grosse; et al. (Ambio, 2022)
Arctic warming is causing ancient perennially frozen ground (permafrost) to thaw, resulting in ground collapse, and reshaping of landscapes. This threatens Arctic peoples' infrastructure, cultural sites, and land-based natural resources. Terrestrial permafrost thaw and ongoing intensification of hydrological cycles also enhance the amount and alter the type of organic carbon (OC) delivered from land to Arctic nearshore environments. These changes may affect coastal processes, food web dynamics and marine resources on which many traditional ways of life rely. Here, we examine how future projected increases in runoff and permafrost thaw from two permafrost-dominated Siberian watersheds—the Kolyma and Lena, may alter carbon turnover rates and OC distributions through river networks. We demonstrate that the unique composition of terrestrial permafrost-derived OC can cause significant increases to aquatic carbon degradation rates (20 to 60% faster rates with 1% permafrost OC). We compile results on aquatic OC degradation and examine how strengthening Arctic hydrological cycles may increase the connectivity between terrestrial landscapes and receiving nearshore ecosystems, with potential ramifications for coastal carbon budgets and ecosystem structure. To address the future challenges Arctic coastal communities will face, we argue that it will become essential to consider how nearshore ecosystems will respond to changing coastal inputs and identify how these may affect the resiliency and availability of essential food resources.

A comprehensive phenotypic characterization of a whole-body Wdr45 knock-out mouse - Caroline A. Biagosch; Silvia Vidali; Michael Faerberboeck; Svenja-Viola Hensler; Lore Becker; Oana V. Amarie; Antonio Aguilar-Pimentel; Lillian Garrett; Tanja Klein-Rodewald; Birgit Rathkolb; Enrica Zanuttigh; Julia Calzada-Wack; et al. (Mammalian Genome, 2021)
Pathogenic variants in the WDR45 (OMIM: 300,526) gene on chromosome Xp11 are the genetic cause of a rare neurological disorder characterized by increased iron deposition in the basal ganglia. As WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, the disease has been named Beta-Propeller Protein-Associated Neurodegeneration (BPAN). BPAN represents one of the four most common forms of Neurodegeneration with Brain Iron Accumulation (NBIA). In the current study, we generated and characterized a whole-body Wdr45 knock-out (KO) mouse model. The model, developed using TALENs, presents a 20-bp deletion in exon 2 of Wdr45 . Homozygous females and hemizygous males are viable, proving that systemic depletion of Wdr45 does not impair viability and male fertility in mice. The in-depth phenotypic characterization of the mouse model revealed neuropathology signs at four months of age, neurodegeneration progressing with ageing, hearing and visual impairment, specific haematological alterations, but no brain iron accumulation. Biochemically, Wdr45 KO mice presented with decreased complex I (CI) activity in the brain, suggesting that mitochondrial dysfunction accompanies Wdr45 deficiency. Overall, the systemic Wdr45 KO described here complements the two mouse models previously reported in the literature (PMIDs: 26,000,824, 31,204,559) and represents an additional robust model to investigate the pathophysiology of BPAN and to test therapeutic strategies for the disease.

Missense and truncating variants in CHD5 in a dominant neurodevelopmental disorder with intellectual disability, behavioral disturbances, and epilepsy - Ilaria Parenti; Daphné Lehalle; Caroline Nava; Erin Torti; Elsa Leitão; Richard Person; Takeshi Mizuguchi; Naomichi Matsumoto; Mitsuhiro Kato; Kazuyuki Nakamura; Stella A. de Man; Heidi Cope; et al. (Human Genetics, 2021)
Located in the critical 1p36 microdeletion region, the chromodomain helicase DNA-binding protein 5 ( CHD5 ) gene encodes a subunit of the nucleosome remodeling and deacetylation (NuRD) complex required for neuronal development. Pathogenic variants in six of nine chromodomain (CHD) genes cause autosomal dominant neurodevelopmental disorders, while CHD5 -related disorders are still unknown. Thanks to GeneMatcher and international collaborations, we assembled a cohort of 16 unrelated individuals harboring heterozygous CHD5 variants, all identified by exome sequencing. Twelve patients had de novo CHD5 variants, including ten missense and two splice site variants. Three familial cases had nonsense or missense variants segregating with speech delay, learning disabilities, and/or craniosynostosis. One patient carried a frameshift variant of unknown inheritance due to unavailability of the father. The most common clinical features included language deficits (81%), behavioral symptoms (69%), intellectual disability (64%), epilepsy (62%), and motor delay (56%). Epilepsy types were variable, with West syndrome observed in three patients, generalized tonic–clonic seizures in two, and other subtypes observed in one individual each. Our findings suggest that, in line with other CHD-related disorders, heterozygous CHD5 variants are associated with a variable neurodevelopmental syndrome that includes intellectual disability with speech delay, epilepsy, and behavioral problems as main features.

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection - Jared Lee; Ji-Young Lee; Christina S. Meade; Michael Cohn; Antonio Chahine; Samantha E. Dilworth; Jessica F. Magidson; Hetta Gouse; Dietmar Fuchs; Adam W. Carrico (Journal of NeuroVirology, 2020)

Aiming for the top: non-cell autonomous control of shoot stem cells in Arabidopsis - Michael Fuchs; Jan U. Lohmann (Journal of Plant Research, 2020)
In multicellular organisms, not all cells are created equal. Instead, organismal complexity is achieved by specialisation and division of labour between distinct cell types. Therefore, the organism depends on the presence, correct proportion and function of all cell types. It follows that early development is geared towards setting up the basic body plan and to specify cell lineages. Since plants employ a post-embryonic mode of development, the continuous growth and addition of new organs require a source of new cells, as well as a strict regulation of cellular composition throughout the entire life-cycle. To meet these demands, evolution has brought about complex regulatory systems to maintain and control continuously active stem cell systems. Here, we review recent work on the mechanisms of non cell-autonomous control of shoot stem cells in the model plant Arabidopsis thaliana with a strong focus on the cell-to-cell mobility and function of the WUSCHEL homeodomain transcription factor.

Journal Club - Volkmar Braun; Georg Fuchs; Michael Schloter; Torsten Schubert; Jochen Graw; Daniela Kruck; Johannes Sander; Gerhart Drews; Stefan Schild; Klaus Hantke; Sandra Wiegand; Alexander Westermann; et al. (BIOspektrum, 2020)

Game characteristics in elite para table tennis - Michael Fuchs; Irene Renate Faber; Martin Lames (German Journal of Exercise and Sport Research, 2019)

Tryptophan-kynurenine profile in pediatric autoimmune hepatitis - Simon D. Lytton; Marcin Osiecki; MałgorzataWoźniak; Bożena Cukrowska; Aldona Wierzbicka; Maria Goliszek; Piotr Socha; Wojciech Janczyk; Dilek Dayanakli; Dieter Abendroth; Sabine Kramp; Kai Fechner; et al. (Immunologic Research, 2019)

Tryptophan metabolism and its relationship with central nervous system toxicity in people living with HIV switching from efavirenz to dolutegravir - Michael R. Keegan; Alan Winston; Chris Higgs; Dietmar Fuchs; Adriano Boasso; Mark Nelson (Journal of NeuroVirology, 2019)

The AlpArray Seismic Network: A Large-Scale European Experiment to Image the Alpine Orogen - György Hetényi; Irene Molinari; John Clinton; Götz Bokelmann; István Bondár; Wayne C. Crawford; Jean-Xavier Dessa; Cécile Doubre; Wolfgang Friederich; Florian Fuchs; Domenico Giardini; Zoltán Gráczer; et al. (Surveys in Geophysics, 2018)

Statistical landslide susceptibility assessment in a dynamic environment: A case study for Lanzhou City, Gansu Province, NW China - Jewgenij Torizin; Li-chao Wang; Michael Fuchs; Bin Tong; Dirk Balzer; Li-qin Wan; Dirk Kuhn; Ang Li; Liang Chen (Journal of Mountain Science, 2018)

Cut of OPEX—Sophisticated Technical Solutions for Hot Strip Mills - Stephan Krämer; Wolfgang Fuchs; Heiko Reichel; Christopher Klein; Angela Ante; Michael Degner (BHM Berg- und Hüttenmännische Monatshefte, 2018)

Statistical landslide susceptibility assessment of the Mansehra and Torghar districts, Khyber Pakhtunkhwa Province, Pakistan - Jewgenij Torizin; Michael Fuchs; Adnan Alam Awan; Ijaz Ahmad; Sardar Saeed Akhtar; Simon Sadiq; Asif Razzak; Daniel Weggenmann; Faseeh Fawad; Nimra Khalid; Faisan Sabir; Ahsan Jamal Khan (Natural Hazards, 2017)

Relatedness of wildlife and livestock avian isolates of the nosocomial pathogen Acinetobacter baumannii to lineages spread in hospitals worldwide - Gottfried Wilharm; Evelyn Skiebe; Paul G. Higgins; Marie T. Poppel; Ulrike Blaschke; Sarah Leser; Christine Heider; Magdalena Heindorf; Paul Brauner; Udo Jäckel; Karin Böhland; Christiane Cuny; et al. (Environmental Microbiology, 2017)
Summary The natural habitats and potential reservoirs of the nosocomial pathogen Acinetobacter baumannii are poorly defined. Here, we put forth and tested the hypothesis of avian reservoirs of A . baumannii . We screened tracheal and rectal swab samples from livestock (chicken, geese) and wild birds (white stork nestlings) and isolated A . baumannii from 3% of sampled chicken ( n = 220), 8% of geese ( n = 40) and 25% of white stork nestlings ( n = 661). Virulence of selected avian A . baumannii isolates was comparable to that of clinical isolates in the Galleria mellonella infection model. Whole genome sequencing revealed the close relationship of an antibiotic‐susceptible chicken isolate from Germany with a multidrug‐resistant human clinical isolate from China and additional linkages between livestock isolates and human clinical isolates related to international clonal lineages. Moreover, we identified stork isolates related to human clinical isolates from the United States. Multilocus sequence typing disclosed further kinship between avian and human isolates. Avian isolates do not form a distinct clade within the phylogeny of A . baumannii , instead they diverge into different lineages. Further, we provide evidence that A . baumannii is constantly present in the habitats occupied by storks. Collectively, our study suggests A . baumannii could be a zoonotic organism that may disseminate into livestock.

Empirische Verfahren zur Ableitung verschiedener Porositätsarten aus Durchlässigkeitsbeiwert und Ungleichkörnigkeitszahl – ein Überblick - Sven Fuchs; Michael Ziesche; Peter Nillert (Grundwasser, 2017)

Lithological mapping with multispectral data – setup and application of a spectral database for rocks in the Balakot area, Northern Pakistan - Michael Fuchs; Adnan A. Awan; Sardar S. Akhtar; Ijaz Ahmad; Simon Sadiq; Asif Razzak; Naghmah Haider (Journal of Mountain Science, 2017)

First record of a xiphoteuthidid coleoid (Cephalopoda: Aulacoceratida) from the Germanic Triassic (Erfurt Formation, Ladinian) - Günter Schweigert; Dirk Fuchs; Hans Michael Salomon (PalZ, 2016)

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation - Sibylle Sabrautzki; Michael A. Sandholzer; Bettina Lorenz-Depiereux; Robert Brommage; Gerhard Przemeck; Ingrid L. Vargas Panesso; Alexandra Vernaleken; Lillian Garrett; Katharina Baron; Ali O. Yildirim; Jan Rozman; Birgit Rathkolb; et al. (Mammalian Genome, 2016)

Cirrhotic patients have good insight into their daily functional impairment despite prior hepatic encephalopathy: comparison with PROMIS norms - Jasmohan S. Bajaj; Melanie B. White; Ariel B. Unser; Dinesh Ganapathy; Andrew Fagan; Edith A. Gavis; Richard K. Sterling; Douglas M. Heuman; Scott Matherly; Puneet Puri; Arun J. Sanyal; Velimir Luketic; et al. (Metabolic Brain Disease, 2016)

An integrative approach for regional landslide susceptibility assessment using weight of evidence method: a case study of Yom River Basin, Phrae Province, Northern Thailand - Suree Teerarungsigul; Jewgenij Torizin; Michael Fuchs; Friedrich Kühn; Chongpan Chonglakmani (Landslides, 2016)

Comparison of bacterial communities on limnic versus coastal marine particles reveals profound differences in colonization - Mina Bižić‐Ionescu; Michael Zeder; Danny Ionescu; Sandi Orlić; Bernhard M. Fuchs; Hans‐Peter Grossart; Rudolf Amann (Environmental Microbiology, 2015)
Summary Marine and limnic particles are hotspots of organic matter mineralization significantly affecting biogeochemical element cycling. Fluorescence in‐situ hybridization and pyrosequencing of 16S rRNA genes were combined to investigate bacterial diversity and community composition on limnic and coastal marine particles > 5 and > 10 μm respectively. Limnic particles were more abundant (average: 1 × 10 7 l −1 ), smaller in size (average areas: 471 versus 2050 μm 2 ) and more densely colonized (average densities: 7.3 versus 3.6 cells 100 μm −2 ) than marine ones. Limnic particle‐associated ( PA ) bacteria harboured A lphaproteobacteria and B etaproteobacteria , and unlike previously suggested sizeable populations of G ammaproteobacteria , A ctinobacteria and B acteroidetes . Marine particles were colonized by P lanctomycetes and B etaproteobacteria additionally to A lphaproteobacteria , B acteroidetes and G ammaproteobacteria . Large differences in individual particle colonization could be detected. High‐throughput sequencing revealed a significant overlap of PA and free‐living ( FL ) bacteria highlighting an underestimated connectivity between both fractions. PA bacteria were in 14/21 cases more diverse than FL bacteria, reflecting a high heterogeneity in the particle microenvironment. We propose that a ratio of Chao 1 indices of PA / FL PA communities of both environments differ substantially.

Enhancement of functional connectivity, working memory and inhibitory control on multi-modal brain MR imaging with Rifaximin in Cirrhosis: Implications for the gut-liver-brain axis - Vishwadeep Ahluwalia; James B. Wade; Douglas M. Heuman; Thomas A. Hammeke; Arun J. Sanyal; Richard K. Sterling; R. Todd Stravitz; Velimir Luketic; Mohammad S. Siddiqui; Puneet Puri; Michael Fuchs; Micheal J. Lennon; et al. (Metabolic Brain Disease, 2014)

The effect of reboxetine co-administration with olanzapine on metabolic and endocrine profile in schizophrenia patients - Avi Amrami-Weizman; Rachel Maayan; Irit Gil-Ad; Artashez Pashinian; Camil Fuchs; Moshe Kotler; Michael Poyurovsky (Psychopharmacology, 2013)

Hair trace elementary profiles in aging rodents and primates: links to altered cell homeodynamics and disease - Mirela Ambeskovic; Eberhard Fuchs; Pierre Beaumier; Michael Gerken; Gerlinde A. Metz (Biogerontology, 2013)

Reducing antipsychotic-induced weight gain in schizophrenia: a double-blind placebo-controlled study of reboxetine–betahistine combination - Michael Poyurovsky; Camil Fuchs; Artashez Pashinian; Adva Levi; Ronit Weizman; Abraham Weizman (Psychopharmacology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Kommentar zum Beitrag „Auswirkungen von Messunsicherheiten bei der Korngrößenanalyse auf die Berechnung des Durchlässigkeitsbeiwertes“ von Matthes et al. (2012) in Grundwasser 17(2), 105–111 - Sven Fuchs; Peter Nillert; Michael Ziesche (Grundwasser, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

A dietary pattern that is associated with C-peptide and risk of colorectal cancer in women - Teresa T. Fung; Frank B. Hu; Matthias Schulze; Michael Pollak; Tianying Wu; Charles S. Fuchs; Edward Giovannucci (Cancer Causes & Control, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Genomic content of uncultured Bacteroidetes from contrasting oceanic provinces in the North Atlantic Ocean - Paola R. Gómez‐Pereira; Margarete Schüler; Bernhard M. Fuchs; Christin Bennke; Hanno Teeling; Jost Waldmann; Michael Richter; Valérie Barbe; Elodie Bataille; Frank Oliver Glöckner; Rudolf Amann (Environmental Microbiology, 2012)
Summary Bacteroidetes are widespread in marine systems where they play a crucial role in organic matter degradation. Whole genome analysis of several strains has revealed a broad glycolytic and proteolytic potential. In this study, we used a targeted metagenomic approach to investigate the degradation capabilities of distinct Bacteroidetes clades from two contrasting regions of the North Atlantic Ocean, the Polar Biome (BPLR) and the North Atlantic Subtropical (NAST). We present here the analysis of 76 Bacteroidetes fosmids, of which 28 encode the 16S rRNA gene as phylogenetic marker, and their comparison to complete Bacteroidetes genomes. Almost all of the 16S rRNA harbouring fosmids belonged to clades that we previously identified in BPLR and NAST. The majority of sequenced fosmids could be assigned to Bacteroidetes affiliated with the class Flavobacteria . We also present novel genomic information on the classes Cytophagia and Sphingobacteria , suggesting a capability of the latter for attachment to algal surfaces. In our fosmid set we identified a larger potential for polysaccharide degradation and cell surface attachment in the phytoplankton‐rich BPLR. Particularly, two flavobacterial fosmids, one affiliated with the genus Polaribacter , showed a whole armoury of enzymes that likely function in degradation of sulfated polysaccharides known to be major constituents of phytoplankton cell walls. Genes involved in protein and peptidoglycan degradation, although present in both fosmid sets, seemed to have a slight preponderance in NAST. This study provides support for the hypothesis of a distinct specialization among marine Bacteroidetes for the degradation of certain types of polymers.

A prospective study of intakes of zinc and heme iron and colorectal cancer risk in men and women - Xuehong Zhang; Edward L. Giovannucci; Stephanie A. Smith-Warner; Kana Wu; Charles S. Fuchs; Michael Pollak; Walter C. Willett; Jing Ma (Cancer Causes & Control, 2011)

Cognitively preserved MS patients demonstrate functional differences in processing neutral and emotional faces - Margit Jehna; Christian Langkammer; Mirja Wallner-Blazek; Christa Neuper; Marisa Loitfelder; Stefan Ropele; Siegrid Fuchs; Michael Khalil; Aga Pluta-Fuerst; Franz Fazekas; Christian Enzinger (Brain Imaging and Behavior, 2011)

Impulswellen infolge Lawineneinstoß in den Speicher Kühtai - Helge Fuchs; Michael Pfister; Robert Boes; Sebastian Perzlmaier; Robert Reindl (WASSERWIRTSCHAFT, 2011)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

A combined computational and experimental investigation of the [2Fe–2S] cluster in biotin synthase - Michael G. G. Fuchs; Franc Meyer; Ulf Ryde (JBIC Journal of Biological Inorganic Chemistry, 2010)

Intraspecific hybrids of Arabidopsis thaliana revealed no gross alterations in endopolyploidy, DNA methylation, histone modifications and transcript levels - Ali Mohammad Banaei Moghaddam; Jörg Fuchs; Tobias Czauderna; Andreas Houben; Michael Florian Mette (Theoretical and Applied Genetics, 2010)

Einsatz des nofdp IDSS im Rahmen der Konzeption naturverträglicher Hochwasserschutzmaßnahmen an der Mümling - Kaj Lippert; Michael Haase; Thorsten Hens; Monika Thül; Elmar Fuchs; Peter Horchler; Christoph Hübner; Manfred Ostrowski; Stephan Rosenzweig; Matthias Sottong; Axel Winterscheid (WASSERWIRTSCHAFT, 2009)

nofdp IDSS — ein kostenfreies Softwareprodukt zur Konzeption von naturverträglichen Hochwasserschutzmaßnahmen - Axel Winterscheid; Elmar Fuchs; Michael Haase; Thorsten Hens; Peter Horchler; Christoph Hübner; Piet van Iersel; Kaj Lippert; Manfred Ostrowski; Stephan Rosenzweig; Monika Thül (WASSERWIRTSCHAFT, 2009)

Überprüfung von Abflusskurven an Pegeln mittlerer und kleinerer Flüsse unter Verwendung hydraulischer 2-D-Modelle - Matthias Bleck; Christian Fuchs; Werner Follardt; Ralf-Michael Umlauf (WASSERWIRTSCHAFT, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Attenuating effect of reboxetine on appetite and weight gain in olanzapine-treated schizophrenia patients: a double-blind placebo-controlled study - Michael Poyurovsky; Camil Fuchs; Artashez Pashinian; Aya Levi; Sarit Faragian; Rachel Maayan; Irit Gil-Ad (Psychopharmacology, 2007)

Effects of turbulence‐mediated larval behavior on larval supply and settlement in tidal currents - Heidi L. Fuchs; Michael G. Neubert; Lauren S. Mullineaux (Limnology and Oceanography, 2007)
Intertidal gastropod larvae retract their vela and sink in strong turbulence, and this behavior potentially increases settlement in turbulent coastal habitats. We incorporated turbulence‐induced sinking behavior of mud snail larvae ( Ilyanassa obsoleta ) in a vertical advection‐diffusion model to characterize behavioral effects on larval supply and settlement in a tidal channel. Throughout flood and ebb tides, larvae that sink in turbulence have higher near‐bed concentrations than passive larvae. This high supply of larvae enables behaving larvae to settle more successfully than passive larvae in strong currents characteristic of tidal inlets. Unlike passive larvae, those that sink in turbulence settle more successfully in stronger currents than in weaker ones and would concentrate their settlement in energetic tidal zones. Turbulence‐mediated behavior may give intertidal larvae a greater ability to select habitats and may reduce larval mortality rates due to settlement failure.

Avalanche Hazard Mitigation Strategies Assessed by Cost Effectiveness Analyses and Cost Benefit Analyses—evidence from Davos, Switzerland - Sven Fuchs; Magdalena Thöni; Maria Christina McAlpin; Urs Gruber; Michael Bründl (Natural Hazards, 2007)

Effects of increased cellular zinc levels on gene and protein expression in HT-29 cells - Birgit Kindermann; Frank Döring; Dagmar Fuchs; Michael W. Pfaffl; Hannelore Daniel (BioMetals, 2005)

Cloning and characterization of SK2 channel from chicken short hair cells - TM Matthews; RK Duncan; M Zidanic; TH Michael; PA Fuchs (Journal of Comparative Physiology A, 2005)

Damage Potential and Losses Resulting from Snow Avalanches in Settlements of the Canton of Grisons, Switzerland - Sven Fuchs; Michael Brndl (Natural Hazards, 2005)

Evaluation of sLORETA in the Presence of Noise and Multiple Sources - Michael Wagner; Manfred Fuchs; Jörn Kastner (Brain Topography, 2004)

Autotrophic CO2 fixation pathways in archaea (Crenarchaeota) - Michael Hügler; Harald Huber; Karl Otto Stetter; Georg Fuchs (Archives of Microbiology, 2003)

Phylogeny and in situ identification of a morphologically conspicuous bacterium, Candidatus Magnospira bakii, present at very low frequency in activated sludge - Jiri Snaidr; Bernhard Fuchs; Günter Wallner; Michael Wagner; Karl‐Heinz Schleifer; Rudolf Amann (Environmental Microbiology, 1999)
A morphologically conspicuous bacterium that constituted a very small fraction ( In situ hybridization with the group‐specific, rRNA‐targeted oligonucleotide probe CF319a indicated a phylogenetic affiliation to the Cytophaga–Flexibacter group of the Cytophaga – Flavobacterium–Bacteroides phylum. Based on strong morphological resemblance to members of the genus Saprospira , additional 16S rRNA‐targeted oligonucleotides with more narrow specificity were designed and evaluated for in situ hybridization to the morphotype of interest. Flow cytometric cell sorting based on the fluorescence conferred by probe SGR1425 and forward scatter enabled a physical enrichment of the helical coiled cells. Subsequent polymerase chain reaction (PCR) amplification of 16S rDNA fragments from whole fixed sorted cells with a primer pair based on probes CF319a and SGR1425 resulted in the retrieval of 12 almost identical partial 16S rDNA fragments with sequence similarities among each other of more than 99.2%. In situ hybridizations proved that the sequences that showed the highest similarity (88.4%) to the 16S rRNA of Saprospira grandis were indeed retrieved from the corkscrew‐shaped filaments. The bacterium is likely to be a member of a genus of which no species has been cultured hitherto. It was consequently tentatively named ‘Magnospira bakii’ and has the taxonomic rank of Candidatus Magnospira bakii, as the ultimate taxonomic placement has to await its cultivation. In this study, it was demonstrated that even bacteria occurring at very low frequencies in highly complex environmental samples can be retrieved selectively without cultivation for further molecular analysis.

Transport of Proteolytic Enzymes Across Caco-2 Cell Monolayers - Udo Bock; Corinna Kolac; Gerrit Borchard; Kerstin Koch; Roland Fuchs; Peter Streichhan; Claus-Michael Lehr (Pharmaceutical Research, 1998)

Lectin-Mediated Drug Targeting: Preparation, Binding Characteristics, and Antiproliferative Activity of Wheat Germ Agglutinin Conjugated Doxorubicin on Caco-2 Cells - Michael Wirth; Andrea Fuchs; Michaela Wolf; Bernhard Ertl; Franz Gabor (Pharmaceutical Research, 1998)